Association between cortical auditory evoked potentials recorded directly through cochlear implants and post-implantation auditory and speech outcomes - HabibAllah, Suhail; Attias, Joseph (Frontiers in Neuroscience, 2026)
IntroductionFollowing the demonstration of feasibility in recording electrically evoked cortical auditory evoked potentials (eCAEPs) directly via cochlear implants in both children and adults, the present(CIs), this study aimed to investigate the relationship between eCAEP waveform characteristics and auditory and speech performance among cochlear implant (CI) users. Additionally, the effects of age at implantation and current age on the latencies and amplitudes of the P1, N1, and P2 complex were evaluated, within the framework of developmental auditory cortical plasticity.MethodsThe study included 25 children (mean age 11.5 ± 4 years) and 12 adults; (mean age 33.8 ± 12.3 years), all bilaterally implanted with Advanced Bionics devices. Intracochlear eCAEPs were recorded from 33 implanted ears in children and 21 ears in adults. Recordings were obtained via the contralateral basal electrode (number 13) in response to brief (10 ms) electrical stimulation of the apical electrode of the stimulated CI while recordings were done via basal electrode number 13 of the contralateral recording CI referenced to the CI case. Each recording session lasted approximately 5 minutes. Children ranged in age from 2.7 to 16.7 years (mean: 11.5 ± 4), and adults from 18.5 to 49.1 years (mean: 33.8 ± 12.3). Age at implantation ranged from 0.5 to 8.1 years in children (mean: averaged 1.75 ± 1.4), and from 1.6 to 43.6 years in adults (mean: for children and 23.5 ± 16.6) years for adults. Speech and auditory performance were assessed using CAP, SIR, and monosyllabic word recognition in quiet and noise.ResultsReliable eCAEPs with all obligatory components were recorded in all ears. Children demonstrated significantly shorter P1-N1 latencies and larger amplitudes compared to the adult cohort in this study. Age at implantation was the strongest predictor of cortical latency, with earlier implantation correlating with shorter P1-N1 latencies. Most children exhibited age-appropriate P1 latencies comparable to normal-hearing peers, whereas only a few adults-those implanted in early childhood-showed similar patterns. In addition, adult responses frequently showed displayed a split P2 waveform, less prominent in children, possibly reflecting altered cortical integration. Notably, significant correlations were found between eCAEP latencies and speech perception scores, particularly in noise, suggesting functional relevance of cortical processing efficiency. Participants with higher CAP and SIR scores exhibited significantly shorter P1-N1 latencies.DiscussionThese findings provide near-field neurophysiological evidence supporting the critical role of sensitive periods in auditory cortical development. The results underscore the value of intracochlear eCAEPs as a neuroscience-based, objective biomarker of auditory cortical function and plasticity in CI users. This approach enables real-time monitoring of neuroplastic changes and offers a novel platform for translational auditory neuroscience in both pediatric and adult implant recipients.